Unlawful Actions of a Notary in Making a Deed of Change in the Management of the Putra Jaya Limited Liability Company (CV). - Anggi Agustriani Putri (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Notaries in carrying out their duties are based on statutory regulations which are often called the Notary Position Law (UUJN) Number 2 of 2014 Jo. Law Number 30 of 2004, in fact, notaries are often found who violate the Notary Position Law, such as in the case of decision Number 2604 K/Pdt/2019, Notary Herminda Br. Ginting, S.H became the defendant because he made an authentic deed of changes in the management of a limited liability company (CV) without the complete presence of an observer. The formulation of the research problem is what is the unlawful act of a notary in making an authentic deed without the presence of a complete observer?, using normative juridical research methods , it can be concluded that notary Herminda Br.Ginting committed an unlawful act because in making a deed of change in the management of a limited liability company (CV) putra jaya he violated article 16 paragraph 1 letter (m) and article 44 of the Law on Notary Positions which resulted in the deed being made being legally flawed and becoming invalid. for the sake of law and causing losses to other people in accordance with article 1365 of the Civil Code "any unlawful act that brings loss to another person, requires the person who wrongly issued the loss, to compensate for the loss", the notary should be careful in writing an authentic deed because the deed The authentication made by the notary has perfect law-making power.